The Impact of Applying the Servant Leadership Style among Educators in Educational Institutes: A Scoping Review - Mohamad Rohieszan bin Ramdan, Khoo Yin Yin, Norsamsinar binti Samsudin, Chamil Arkhasa Nikko bin Mazlan, Norimah binti Rambeli @ Ramli (Tanjung Malim, 2024)
The Impact of Applying the Servant Leadership Style among Educators in Educational Institutes: A Scoping Review by Mohamad Rohieszan bin Ramdan, Khoo Yin Yin, Norsamsinar binti Samsudin, Chamil Arkhasa Nikko bin Mazlan, Norimah binti Rambeli @ Ramli